The effect of synovium graft on conjunctiva in rabbit model of dry eye - Keungjin Park; Kyungmin Nam; Min Jang; Won-Jae Lee; Seong Mok Jeong; Seulgi Bae; Young-Sam Kwon; Sae-Kwang Ku; Sungho Yun (The Korean Society of Animal Reproduction and Biotechnology, 2021)
This study was performed to identify the effect of synovium graft on conjunctiva in rabbits after dry eye induction. Six New Zealand White rabbits were used as dry eye models. Both eyes were divided to two groups as control and synovium graft group. The synovium graft was performed in fourth week after dry eye modeling. Quantitative change of tears through Schirmer tear test (STT), qualitative change of tear film through tear film break up time (TFBUT), and damage of cornea through fluorescein staining were observed for 10 weeks at intervals of two weeks. Histological examination was performed to evaluate cornea and conjunctiva at tenth week. In both groups, STT and TFBUT were significantly decreased in 4 weeks after modeling compared to 0 weeks (p < 0.05) . After synovium graft, there were increases in STT value at 4 weeks and TFBUT at 4 and 6 weeks in graft group (p < 0.05). Corneal fluorescein staining showed no significant difference between the two groups. In histopathological examination, grafted synovium was detected as round to ovoid ingression folds, well attached to grafted regions with 0.11 ± 0.04 mm2 (range, 0.05- 0.16 mm2). These results indicated that the synovium graft on the conjunctiva had an effect on the qualitative and quantitative improvement of the tear film even though there was no histological change.